Ormas Islam dan Isu Keislaman di Media Massa - Niam, Khoirun (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
The research aims to present Islamic issues reported by by Koran Kompas, Jawa Pos, and Surya during 2012 throughout 2012, especially concerning to Islam and violence, law and politic. The study shows that (1) there are 741 news related to Islam during 2012, with details of 198 within first period (January-April), 262 within second period (May-August), and 281 within third period (September-De–cember). Moreover, Islamic Social Organizations have more chances to induce legal and politic process, and violence. Therefore, it is important to empower Islamic social orga–nization and in doing so as partner for building good civilization.Keywords: Islamic social organization, mass media, Islam, violence, law and politic.———————————————————————-Penelitian ini bertujuan untuk menyajikan isu-isu Islam yang diberitakan oleh Koran Kompas, Jawa Pos, dan Surya selama 2012, terutama mengenai Islam dan kekerasan, hukum dan politik. Studi ini menunjukkan, bahwa dalam pemberitaan di tiga media cetak tersebut (1) ada 741 berita berhubungan dengan Islam dengan rincian 198 (Januari-April), 262 (Mei- Agustus), dan 281 (September-Desember). Selain itu, organisasi sosial Islam memiliki lebih banyak kesempatan untuk menginduksi proses hukum dan politik, dan kekerasan. Oleh karena itu, memberdayakan organisasi sosial Islam sekaligus menjadikannya sebagai mitra merupa–kan hal pemtimg untuk membangun peradaban yang baik.Kata Kunci: Organisasi sosial Islam, mass media, Islam, kekerasan, hukum dan politik